STABILITAS PLASMA LIOFILISAT BUATAN SENDIRI SEBAGAI BAHAN KONTROL KUALITAS PADA LABORATORIUM KIMIA KLINIK TERHADAP PEMERIKSAAN TOTAL PROTEIN DAN ALBUMIN - Putri Safira Firdaus (Analis Kesehatan Sains, 2023)
The stability test of the control material is very important because the stability indicates the control material does not change significantly during storage. The use of commercial control is not economically feasible in many countries because of the unavailability or high cost. Therefore, the manufacture of lyophilized human plasma will be great use to several small and private laboratories, including puskesmas laboratories. This study aims to determine the stability of homemade lyophilized plasma as a quality control agent in a clinical chemistry laboratory on total protein and albumin parameters. This type of research is an experimental research with a time series group design. This research was conducted at the campus laboratory and Pramita Laboratory. Samples were taken from 1 respondent in April - May 2022, stored at a temperature of 2-8°C and checked every week for 8 weeks. The results of the examination of total protein levels mean weeks 1 to 8 were 6,42 mg/dL, 6,65 mg/dL, 6,73 mg/dL, 6,50 mg/dL, 6,25 mg/dL, 6,47 mg/dL, 6,28 mg/dL, 6,28 mg/dL. The results of the examination of albumin levels on average 1 to 8 were 3,99 mg/dL, 3,91 mg/dL, 3,63 mg/dL, 3,80 mg/dL, 3,97 mg/dL, 3,43 mg/dL, 3,60 mg/dL, 3,72 mg/dL. The results Leavy Jenning's chart analysis showed plasma lyophilized test results for total protein and albumin levels were still within the limit of ± 2SD. And in regression test the KD value for Total protein 40.32% and the KD value for Albumin 32.54%, showed that the storage time for total protein and albumin had effect on stability of plasma lyophillized. So it can be concluded the examination of total protein and albumin levels stored at a temperature of 2-8°C was stable for 8 weeks